2019
DOI: 10.1155/2019/3428123
|View full text |Cite
|
Sign up to set email alerts
|

Amplatz versus Balloon for Tract Dilation in Ultrasonographically Guided Percutaneous Nephrolithotomy: A Randomized Clinical Trial

Abstract: Purpose To compare balloon with Amplatz for tract dilation in totally ultrasonographically guided PCNL (UPCN). Methods We randomized 66 patients candidate for sonographically guided PCNL in the flank position in two study groups. In the first group, we used single step Amplatz dilation (AG) technique in which the 28- or 30-French Amplatz dilator is used for tract dilation. In the other group, we dilated the tract using balloon dilator (BG). We compared procedure time, success rate of dilation, and postoperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 20 publications
0
20
2
2
Order By: Relevance
“…This result was quite different from the previous studies [24,25], we do not suggest BD in cases without hydronephrosis for beginners; for such cases, two-step TMD under ultrasound as we previously reported or xray guidance may be a better choice. The cost of the disposable balloon is much higher than that of the TMD in China due to insurance policy; the telescopic metal dilator can be reused, which further lowers the cost of the operation.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This result was quite different from the previous studies [24,25], we do not suggest BD in cases without hydronephrosis for beginners; for such cases, two-step TMD under ultrasound as we previously reported or xray guidance may be a better choice. The cost of the disposable balloon is much higher than that of the TMD in China due to insurance policy; the telescopic metal dilator can be reused, which further lowers the cost of the operation.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, the end of the balloon dilator is taper-shaped and has an approximate tip length of 0.5 cm beyond the taper; so the measured balloon length should exclude the length of the tip to avoid short dilation in patients without hydronephrosis. Pakmanesh H [25] performed a prospective study to check the feasibility of performing USG Guided Balloon dilatation (24 FR) of PCNL tract for access, and they concluded that a higher rate of short dilation occurred in Amplatz dilation compared that with balloon dilation, which were quite different from present study. A poorly dilated calyx was not good for performing ultrasoundguided tract dilation using a balloon dilator.…”
Section: Discussioncontrasting
confidence: 74%
“…On the opposite aspect, Hamid Pakmanesh et al observed that bleeding and different headaches had been comparable inside the balloon and amplatz teams, whereas operative time become longer within the amplatz organization with a higher charge of short dilation. Concerning the approaching the decrease organization calyces, the balloon technique become superior 16 .…”
Section: Discussionmentioning
confidence: 99%
“…At present, the way of tract establishment is Amplatz dilation or balloon dilation. Pakmanesh et al studies have pointed out that although the cost of balloon dilator is higher, it is better than Amplatz dilation in safety and success rate [4]. Recent studies have pointed out that the whole process of establishing the tract with balloon dilator can be monitored by ultrasound, but for patients without hydronephrosis or obesity, there may still be not reached the desired calyx (short dilation) or tract displacement without uoroscopy assistance, resulting in tract establishment failure or bleeding [5].…”
Section: Introductionmentioning
confidence: 99%